Behavioral case formulation and intervention : a functional analytic approach - Sturmey, Peter (Chichester : Wiley, 2008)
There is a long history of behavioral approaches to psychopathology. Recent work, however, has focused instead on cognitive, psychodynamic and integrative approaches. Behavioral Case Formulation and Intervention redresses this imbalance by exploring radical behaviorism and its approach to the conceptualization, case formulation and treatment of psychopathology. Peter Sturmey describes the conceptual foundations of functional approaches to case formulation and intervention, explains the technology and application of behavioral assessment and hypothesis-driven intervention, and identifies outstanding and conceptual and practical problems within this framework.
Keywords: Clinical Psychology; Electronic books